History of Utah Radicalism : Startling, Socialistic, and Decidedly Revolutionary. - McCormick, John S. (Utah State University Press, 2011)
Utah, now one of the most conservative states, has a long tradition of left-wing radicalism. Early Mormon settlers set a precedent with the United Order and other experiments with a socialistic economy. The tradition continued into the more recent past with New Left, anti-apartheid, and other radicals. Throughout, Utah radicalism usually reflected national and international developments. Recounting its long history, McCormick and Sillito focus especially on the Socialist Party of America, which reached a peak of political influence in the first two decades of the twentieth century - in Uta.